2021
DOI: 10.1128/jvi.00610-21
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping and Transcriptional Profiling of Human Plasmablasts in Dengue

Abstract: Plasmablasts represent a specialized class of antibody secreting effector B cell population that transiently appear in blood circulation following infection or vaccination. The expansion of these cells generally tends to be massive in patients with systemic infections leading to viral hemorrhagic fevers such as dengue or ebola. To gain a detailed understanding of the human plasmablast responses beyond antibody expression, here we performed immunophenotyping and RNA seq analysis of the plasmablasts from dengue … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
1
3
0
Order By: Relevance
“…Our study, along with others, has provided evidence documenting the potential migratory functions of B cell subsets to tissues during acute DENV infection [ [14] , [15] , [16] ]. A previous report has demonstrated that PCs and PBs showed the up-regulation of inflamed tissue-homing molecules, CXCR3 and CCR2, on ASCs, but not CCR10, a chemokine receptor suggested for its role in skin-homing [ 15 ].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Our study, along with others, has provided evidence documenting the potential migratory functions of B cell subsets to tissues during acute DENV infection [ [14] , [15] , [16] ]. A previous report has demonstrated that PCs and PBs showed the up-regulation of inflamed tissue-homing molecules, CXCR3 and CCR2, on ASCs, but not CCR10, a chemokine receptor suggested for its role in skin-homing [ 15 ].…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, during the acute phase of secondary DENV infection, there is typically a massive expansion of plasma cells (PCs) and plasmablasts (PBs), differentiated forms of B cells capable of secreting antibodies (also known as antibody secreting cells or ASCs) [ 12 , 13 ]. These peripheral PCs and PBs have been shown to be cross-reactive DENV-specific ASCs that represent only a minor portion of memory B cell pool [ 12 , 14 ]. Nevertheless, their origin, function, and tissue homeostasis remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations